2015
DOI: 10.1097/mao.0000000000000695
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Headband Assessment for Semi-Implantable Bone Conduction Hearing Devices in Conductive Hearing Loss

Abstract: BC thresholds may be a better indicator of implant performance than headband assessment. Candidacy assessment for siBCI implantation that relies on headband testing with pBCI processors should be interpreted with caution because the headband may under-represent the implanted device. This seems to be especially true at 3 kHz and above and may make it difficult for surgeons to conduct accurate informed consent discussions with patients about the realistic anticipated outcomes and benefits of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The preoperative and postoperative results can be seen in the S2 Table. Speech understanding in quiet was assessed in 27 publications [16, 26, 27, 7, 28, 22, 29, 24, 30, 10, 31, 25, 3234, 18, 12, 13, 35, 36, 20, 14, 37, 38, 21, 39], resulting in a mean unaided WRS score of 25.73±23.64% improving to 84.48±15.09% in the aided condition, resulting in an overall mean improvement of almost 60% (S2 Table).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preoperative and postoperative results can be seen in the S2 Table. Speech understanding in quiet was assessed in 27 publications [16, 26, 27, 7, 28, 22, 29, 24, 30, 10, 31, 25, 3234, 18, 12, 13, 35, 36, 20, 14, 37, 38, 21, 39], resulting in a mean unaided WRS score of 25.73±23.64% improving to 84.48±15.09% in the aided condition, resulting in an overall mean improvement of almost 60% (S2 Table).…”
Section: Resultsmentioning
confidence: 99%
“…The device’s transcutaneous technology avoids several complications found in percutaneous bone conduction implants including skin reaction, growth of skin over the abutment, implant extrusion, and wound infection [47, 44, 34, 46]. The complication rate reported for atBCI recipients was considerably lower with one minor event in 9.9 person-years, compared to other devices, especially percutaneous bone-anchored hearing aids such as the BAHA (Cochlear Limited, Australia)[48].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the BAHS were worn with a headband and had not been implanted. The hearing results achieved with a headband are worse than with semi-implantable devices [ 18 ]. In the BAHS group, the SssdNnh configuration showed an improvement after 1 year with the implanted BAHS that seems to be better than after 3-week testing with a headband.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in keeping with a series from Dalhousie University, Canada, where Rainsbury et al . assessed a series of seven implants (Bonebridge only) and found that the headband assessment underestimated the implanted device 5 . Rainsbury et al .…”
Section: Discussionmentioning
confidence: 99%
“…Rainsbury et al . compared pre-operative softband bone conduction thresholds and speech discrimination scores with post-operative tests using their transcutaneous bone conducting aid in a small sample 5 . They demonstrated a correlation between pre-operative bone conduction thresholds and post-operative aided sound-field thresholds, but not between pre- and post-operative speech testing.…”
Section: Introductionmentioning
confidence: 99%